Words & meanings - Goddard, Cliff
Includes bibliographical references (pages 262-290) and index; Words, Meaning, and Methodology -- Men, Women, and Children: The semantics of basic social categories -- Sweet, Hot, Hard, heavy, Rough, Sharp: Physical quality words in cross-linguistic perspective -- From Colour Words to Visual Semantics: English, Russian, Warlpiri -- Happiness and Human Values in Cross-cultural and Historical Perspective -- Pain Is it a Human Universal? The Perspective From Cross-linguistic Semantics -- Suggesting, Apologising, Complimenting: English speech act verbs -- A Stitch in Time and The Way of The Rice Plant: The semantics of proverbs in English and Malay -- The Meaning of Abstract Nouns: Locke, Bentham and Contemporary Semantics -- Broader Perspectives: Beyond lexical semantics; Ebook from Oxford Scholarship Online